‘In The Pipeline’: Highlighting Political Propaganda In Ghana Through Drama - Afful, G.K. (University of Ghana, 2017)
This work is an academic exercise undertaken for my master’s degree – MFA- at the School of Performing Art, University of Ghana. The study examines the phenomenon of political propaganda campaign in contemporary Ghana from the standpoint of drama since 1992. As a playwright, I settled on a play entitled In the Pipeline for my project work. My motivation for such a work derives from personal experience, interviews and observation in Ghana politics; my academic curiosity to analyse political campaign improprieties and also my fervent desire to contribute in awareness creation. Theatre is the medium adopted in this work based on the research I undertook in my study area, and the data collected on political activities at Kintampo District Assembly, and general observation on political situation in our country Ghana. Based on this, I developed a theatrical piece to interrogate, investigate, and critically analyse and evaluate my findings of the research field. My work is a contribution to the existing body of knowledge where drama/theatre is used effectively to conscientize, educate, inform, entertain and critique the Ghanaian political environment.
Thesis (MFA)
Keywords: Pipeline; Political Propaganda; Drama; Ghana